Cryo-EM reveals the asymmetric assembly of squid hemocyanin - Yoshikazu Tanaka; Sanae Kato; Markus Stabrin; Stefan Raunser; Takashi Matsui; Christos Gatsogiannis (IUCrJ, 2019)
The oxygen transporter of molluscs, hemocyanin, consists of long pearl-necklace-like subunits of several globular domains. The subunits assemble in a complex manner to form cylindrical decamers. Typically, the first six domains of each subunit assemble together to form the cylinder wall, while the C-terminal domains form a collar that fills or caps the cylinder. During evolution, various molluscs have been able to fine-tune their oxygen binding by deleting or adding C-terminal domains and adjusting their inner-collar architecture. However, squids have duplicated one of the wall domains of their subunits instead. Here, using cryo-EM and an optimized refinement protocol implemented in SPHIRE, this work tackled the symmetry-mismatched structure of squid hemocyanin, revealing the precise effect of this duplication on its quaternary structure and providing a potential model for its structural evolution.